RANCANG BANGUN LAMPU PENERANGAN JALAN UMUM (PJU) MENGGUNAKAN SOLAR PANEL BERBASIS ANDROID (APLIKASI DI JALAN PARKIRAN KAMPUS 2 UMSIDA) - Hikmawan, Sugik Rizky; Suprayitno, Eko Agus (Elinvo (Electronics, Informatics, and Vocational Education), 2018)
Data from the Directorate General of Electricity and Energy Development in 1997, the installed capacity of solar electricity in Indonesia reaches 0.88 MW from the available potential of 1.2 x 109 MW. Therefore, this research is made of solar street based lighting design (PJU) as alternative energy that cheap and economical. The work system on the street lighting lighting (PJU) is controlled by an Arduino microcontroller. And use solar panel as source of voltage and light sensor. The light sensor will work and read the intensity of sunlight. During the day the sensor provides input to the arduino so that the lights automatically turn off and at night the sensor gives input to the arduino so that the automatic light is on. And can be controlled using Android Gadget through bluethoot HC-05 Module. The result The lights automatically turn on and off according to the reading of the Light Sensor and the Arduino Microcontroller Communications with Android Smartphone leverages the Bluethoot HC-05 module to work properly. Arduino Microcontroller can take orders from Android Smartphone either with obstacle or without obstruction with a maximum distance of 15 meters